'Helping our beneficiaries tell their own stories?' International aid agencies and the politics of voice within news production. (April 2018) - Wright, Kate
International aid agencies often claim to give the poor and disenfranchised a voice by helping them tell their stories to others located far away. But how do aid workers conceptualize and operationalize a politics of voice within media production processes? How do ideas about giving voice to others shape aid agencies' engagement with mainstream news organizations? This article explores two contrasting news production case studies which took place in South Sudan and Mali, involving Save the Children, Christian Aid and their local partners. It finds that different approaches to giving voice exist in aid work, creating tensions within and between agencies. In addition commercialized notions of value for money, the influence of mediated donor reporting, and aid workers' weak understandings of linguistic and intercultural interpretation combined to make aid agencies' values-in-action far less empowering than they assumed.